Structural and Dielectric Properties of Polyurethane Palm Oil Based Filled Empty Fruit Bunch - S. N. S., Mahmud; M. A., Jusoh; You, K. Y.; N., Salim; S., Shaheen; Sutjipto, A. G. E. (AI Publications, 2017)
This paper presents the bunch. Polyurethane filled with empty fruit bunch (PU-EFB) composite was prepared through hot press process. The crystal structure of PU-EFB has been studied using X-ray diffraction technique. The effect of EFB filler content on the microwave dielectric properties of the PU-EFB composites was studied in the X-Band frequency region using Vector Network Analyzerat room temperature. A Kraszewski model showed good correspondence with measured dielectric constant of PUEFB composite, especially at the higher loading level.